Amikacin-containing self-emulsifying delivery systems via pulmonary administration for treatment of bacterial infections of cystic fibrosis patients. (4th May 2018) - Hetényi, Gergely; Griesser, Janine; Fontana, Simon; Gutierrez, Anja Martinez; Ellemunter, Helmut; Niedermayr, Katharina; Szabó, Péter; Bernkop-Schnürch, Andreas
Aim: The aim of the study was to develop self-emulsifying delivery systems (SEDDS) exhibiting improved permeation rate for pulmonary delivery of amikacin for treatment of cystic fibrosis (CF) patients.Materials & methods: Solubility of amikacin in lipids was improved by hydrophobic ion pairing with sodium myristyl sulfate. The complex was loaded into SEDDS. Drug-release studies were performed and the permeation properties of SEDDS through human CF mucus were examined.Results: A total of 10% complex could be loaded into SEDDS. SEDDS exhibited sustained release. Up to twofold more amounts of amikacin permeated through the CF mucus compared with reference.Conclusion: The developed SEDDS with amikacin may be a promising tool for the treatment of certain bacterial infections of CF patients.